Inflammatory cell death induced by 5-aminolevulinic acid-photodynamic therapy initiates anticancer immunity - Wang, Lingyan; Chelakkot, Vipin Shankar; Newhook, Nick; Tucker, Stephanie; Hirasawa, Kensuke (Frontiers in Oncology, 2023)
Inflammatory cell death is a form of programmed cell death that induces inflammatory mediators during the process. The production of inflammatory mediators during cell death is beneficial in standard cancer therapies as it can break the immune silence in cancers and induce anticancer immunity. Photodynamic therapy (PDT) is a cancer therapy with photosensitizer molecules and light sources to destroy cancer cells, which is currently used for treating different types of cancers in clinical settings. In tumor cells, 5-ALA is metabolized to protoporphyrin IX, a photosensitizer. In this study, we investigated if PDT using 5-aminolevulinic (5-ALA-PDT) causes inflammatory cell death and, a subsequent increase in the immunogenicity of cancer cells. We found that 5-ALA-PDT induces inflammatory cell death, but not apoptosis, in mouse breast cancer (4T1) cells and human colon cancer (DLD-1) cells in vitro. Moreover, when mice were pretreated with 5-ALA-PDT culture supernatant, the growth of 4T1 tumors was significantly suppressed compared to those pretreated with freeze and thaw (F/T) 4T1 culture supernatant. These results indicate that 5-ALA-PDT induces inflammatory cell death which promotes anticancer immunity in vivo.